Optimizing Cost Management in Dynamic Business Environments: An In-depth Analysis of Production Cost Budgeting, Considering Specific Elements and External Factors - Suhidayat, Tatang; Ravitilova, Ravitilova; Handayani, Ai; Daniel Tambunan, Fransisco Wanviano (Program Studi Magister Akuntansi, Direktorat Pascasarjana, Universitas Sangga Buana, 2023)
This research discusses the effectiveness of using budgets as a means of controlling production costs at PT. Sari Tuna Makmur in the 2017-2021 period. By examining the budget and realization of direct labor costs (salary costs), factory overhead costs, as well as differences in budgeted tuna production costs, this research aims to identify factors that influence variations between budget and realization. The research results show that the company is generally successful in controlling production costs. Although there are variations in direct labor costs during the COVID-19 pandemic, PT. Sari Tuna Makmur was able to achieve production costs that were lower than the budget in previous years. Internal factors such as business policies, production capacity, and production facilities, as well as external factors such as competition and consumer demand, play an important role in successful cost control. However, special challenges arise during the pandemic, where the decision not to reduce the workforce may result in direct labor cost deviations. Therefore, this research recommends increasing the accuracy of budget preparation and more detailed attention to factors that influence production costs, especially in unexpected situations. This research contributes to the understanding of production cost control strategies amidst the dynamics of the business environment. The practical implication is the need for companies to continue to optimize cost control strategies, consider changes in external conditions, and increase accuracy in preparing budgets to maintain the company's operational and financial sustainability.